Micro-Coevolution of Genetics Rather Than Diet With Enterotype in Pigs - Ma, Ning; Sun, Yiwei; Chen, Jiashun; Qi, Zengkai; Liu, Chunchen; Ma, Xi (Frontiers in Nutrition, 2022)
Based on the characteristic of low diarrhea in native Chinese breeds, we introduce the enterotype model for piglets, which is a new perspective to decipher the colonization and the transition of the gut microbiota among various pig breeds. After eliminating environmental influences represented by diet, the microbiota, mainly shaped by host genetics, is focused. Three representative enterotype clusters were identified, which were represented by Bacteroides, Streptococcus, and Lactobacillus. Chinese native breeds were distributed in enterotype 1 (E1) and E3, which collectively drove the diversification and functionality of the microbial community of various Chinese pig breeds. Next, the Lactobacillus reuteri (L. reuteri), which is the representative strain of E3, was specifically isolated in all three enterotypes. The excellent stress-resistance of L. reuteri-E3 not only highlighted the stronger disease resistance of Chinese breeds but also had a great potential to intervene in weaned piglet diseases. Enterotype classification based on host genetics is much more deterministic and predictable, clarifying the driver of the host-microbiome dynamics and constructing the picture of the micro-coevolution of human host genetics with the gut microbiome.